“Caught in the crossfire” – women veterans’ testimonies regarding excessively violent acts committed in combat zones - HaCohen, Nehama; Amir, Dana (Frontiers in Psychology, 2024)
As women in the Israeli Defense Forces (IDF) are increasingly placed in supportive and combat roles in active war zones, they routinely encounter and participate in violent acts.This study focusses on the centrality of gendered inequality and oppression as a factor that shapes not only women's experience in the military but also their responses in cases of excessive violence. The goal of this study was to explore the ways women veterans of combat or combat-support units conceptualize their stance regarding violent acts which they either committed or witnessed in war zones. Using a qualitative approach, we analyzed the retrospective testimonies of 58 Israeli women veterans from the archives of an NGO that documents veteran combatants exposure to excessive violence. Most women explained their violent acts as inherent to the military system and culture, which in our analysis was categorized as examples of either internalized gender oppression or as identification with the aggressor. A smaller number of women described their attempts to protest, as they took a moral stance rooted in a feminine perspective. The three explanations revealed through the analysis of the testimonies reflect the inner tension experienced by many women in the military, as they navigate between two extreme positions, either as victims of male dominance, or as aggressors that are part of a powerful military system. In this study, gendered inequality provides a framework for analyzing the data. Thus, this study contributes to the theoretical knowledge and methodological approaches concerning violent situations in combat areas, focusing on the various ways in which women veterans subjectively and retroactively conceptualize their participation in and responses to violent acts.